A comparative analysis of the ERP tools, Odoo and Openbravo, for business management (2020)
The comparative analysis of the two (2) enterprise resource planning (ERP) systems, Odoo and Openbravo, was a research work that began with the characterization of the ERP tools, the description of the general characteristics, the functionalities (hardware and software) and the advantages and disadvantages of each ERP system. The criteria for each aspect evaluated were selected under the ERP System Selection Methodology (MSSE) [1], establishing the weights or ratings for each of the functional, technical, vendor, service and economic aspects of each ERP under study, allowing an individual evaluation and comparison of the two (2) systems with the ultimate goal of selecting the highest scoring tool and defining the degree of coupling with the company in the mining sector in Norte de Santander, Cúcuta Colombia. Finally, the conclusions of the research were presented to the research community, as well as to the bibliographic references studied.